Design and Analysis of DC-DC Converters for Photovoltaic Systems - Anish John Paul, M.; Kumar, C. Agees (Asian Journal of Electrical Sciences, 2019)
The solar energy conversion system is an alternative for conventional power generating system. The voltage which is available from solar array is variable and to obtain a stable voltage from solar panels, DC-DC converters are required for constant power production. A PV module is designed in MATLAB-SIMULlNK using the S-function builder and controlled current source. The proposed PV module enables us to obtain its P-V and I-V characteristics at different temperature and radiations. This paper presents the design and simulation of DC-DC converters. In this paper, Boost converter, cascaded Buck Boost and Cuk converter are modelled in MATLAB and their results are compared.